PELAYANAN ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR NEGERI DAN PENDIDIKAN INKLUSIF - Intan Nur Fatma; Desma Banjarnahor; Irna Gita Utami Rangkuti; Novita Frizka (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Inclusive education is an effort to provide equal educational services for all learners, including children with special needs (CSN). However, in practice, the implementation of inclusive education in elementary schools still faces various challenges, particularly related to teacher readiness, instructional methods, and support services. This study aims to describe the forms of educational services provided for children with special needs in elementary schools that implement inclusive education. The research employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation at UPT SD Negeri 067952 Medan Johor. The research subjects included the principal, special education teachers, homeroom teachers, and three students with special needs categorized as having cerebral palsy, ADHD, and Down syndrome. The results indicate that the school has implemented the principles of inclusive education by integrating children with special needs into regular classrooms and providing fair and non-discriminatory treatment. Teachers make efforts to adjust the delivery of instruction and assessment based on the abilities and developmental progress of each student with special needs. In addition, the school’s social environment is considered conducive due to peer support and parental involvement. Nevertheless, the school still faces obstacles in the form of limited facilities and infrastructure, as well as the absence of a structured individualized education program for children with special needs. Therefore, improving teacher competence and developing specialized service programs are necessary to ensure that the implementation of inclusive education can run more optimally. Keywords: Inclusive education; children with special needs; educational services.